2004
DOI: 10.1002/jnr.20356
|View full text |Cite
|
Sign up to set email alerts
|

Neudesin, a novel secreted protein with a unique primary structure and neurotrophic activity

Abstract: We identified a novel secreted protein and named it neudesin. Mouse neudesin of 171 amino acids is unique with no primary structural similarity to any known proteins. The neudesin protein produced in cultured cells was secreted efficiently into the culture medium. Mouse neudesin mRNA was expressed abundantly in the developing brain and spinal cord in embryos, but was expressed widely in postnatal tissues including brain, heart, lung, and kidney. Mouse neudesin mRNA was expressed in neurons but not glial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(127 citation statements)
references
References 25 publications
2
124
0
1
Order By: Relevance
“…4C) (Kimura et al, 2005(Kimura et al, , 2008. In Pgrmc1-knockdown cells, Pgrmc2 transcription increased (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…4C) (Kimura et al, 2005(Kimura et al, , 2008. In Pgrmc1-knockdown cells, Pgrmc2 transcription increased (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Knockdown of RASAL2 decreases ECT2 activity toward RHO in astrocytoma cells and leads to mesenchymal-amoeboid transition, altering the invasive properties of the cells. NENF is a secreted protein with neurotrophic activity expressed abundantly in the developing brain and spinal cord (15). It was shown to induce phosphorylation of ERK1/2 and AKT in primary cultured mouse neurons and MCF-7 breast cancer cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…NENF is a secreted protein with neurotrophic activity expressed abundantly in the developing brain and spinal cord (15). It was shown to induce phosphorylation of ERK1/2 and AKT in primary cultured mouse neurons and MCF-7 breast cancer cells (15). NENF is also highly expressed in several cancers and its overexpression in MCF-7 breast cancer cells increases their tumorigenicity and invasiveness (16).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that hypothalamic signaling pathways in the mouse respond to the human NENF protein. Physiological processes activated by NENF signaling may be evolutionarily conserved since the human and mouse proteins have 91% similarity (31), which suggests that NENF may be a novel candidate biomarker for disease susceptibility or development of novel drug therapeutics in humans.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Several characteristics prompted us to select one candidate protein from this screen for in-depth characterization, neuron-derived neurotrophic factor (Nenf or neudesin). Mouse Nenf contains 171 amino acids, is 91% similar to human NENF, is primarily expressed in neurons, but is absent from glia (31). In addition, it is expressed in white adipose tissue (28).…”
mentioning
confidence: 99%